The role of livestock in the Kenyan economy: Policy analysis using a dynamic Computable General Equilibrium model for Kenya - Engida, Ermias; Guthiga, Paul; Nyota, Hannah; Karugia, Joseph T. (International Food Policy Research Institute, 2015)
The major significance of this study is thus, to give the already existing dynamic CGE model the ability to better treat the livestock sector by capturing its complete natural picture through coupling of the stock–flow feature of the sector into the model.